Bounded-DWA: An Efficient Local Planner for Ackermann-driven Vehicles on Sandy Terrain - Gong, Ke; Xu, Zhiyuan; Zhang, Xinyu (2023 IEEE International Conference on Real-time Computing and Robotics (RCAR), 2023)
We present a new dynamic window approach (DWA) for mobile vehicles equipped with Ackermann steering geometry that adheres to Ackermann kinematic constraints. By integrating these constraints with the sampling window in DWA, we can further reduce and bound the sampling range and enhance the efficiency of the DWA when a mobile vehicle moves on sandy terrain. Furthermore, we improve the evaluation function to optimize the selected trajectory. Our algorithm is successfully validated in ROS and Gazebo through comparison with other existing local planner such as the original DWA and TEB algorithms. We also successfully deploy our Bounded-DWA in the application of coverage path planning, where tree-planting robots traverse on sandy terrain.